Visualization of the mechanosensory machinery in live mammalian auditory hair cells (2021)
The inner ear detects sound-induced vibrations through deflection of rigid projections at the apex of mechanosensory hair cells, known as stereocilia. Stereocilia of a hair cell form the “hair bundle”. Sound is detected when stereocilia are deflected and tug on tiny extracellular tip links that gate mechanotransduction channels. Any study of the potential dynamic changes within this mechano-electrical transduction (MET) machinery is currently challenging due to small sizes of their components, in a range of 5-200 nm. Conventional label-free optical microscopy has a best resolution of ~200 nm. Therefore, it is impossible to visualize the MET apparatus in live cells. Super-resolution imaging has been only of a limited use due to the requirement of fluorescent labeling. Therefore, ultrastructural details of the MET apparatus in the auditory hair cells have been investigated mostly with electron microscopy (EM). Unfortunately, EM techniques require chemical or cryofixation of the sample, making the study of dynamic processes in the MET machinery nearly impossible or extremely labor intensive. In theory, scanning probe techniques, such as atomic force microscopy (AFM), have enough resolution to visualize ultrastructural details in live cells. However, the efforts to image hair cell bundles with AFM were not too encouraging, since stereocilia bundles are usually damaged after even the slightest contact of the AFM probe with them. The hopping probe ion conductance microscopy (HPICM) is an alternative non-contact scanning probe technique capable of performing time lapse imaging of the surface of live cells with a complex topography, with single nanometer resolution and without making physical contact with the sample. The HPICM uses an electrical current passing through a glass nanopipette to detect the cell surface in close vicinity to the pipette, while a 3D-positioning piezoelectric system scans the surface and generates its image. The goal of this project was to optimize HPICM for visualization of nanoscale structures on the surface of the stereocilia in live auditory hair cells. We were able to visualize stereocilia bundles in live inner hair cells including the links interconnecting stereocilia (~5 nm in diameter). We were also able to obtain time-lapse imaging of these bundles. We believe that this is an important step toward our goal of studying ultrastructural changes in the mechanosensory machinery of live hair cells with HPICM.